Influência da cultura no comportamento alimentar de gestantes: contribuições para enfermagem - Junges, Carolina Frescura (2010)
Dietary human choices are linked to many social, cultural, historical, and biological influences. Cultural influences indicate accepted and forbidden foods and translate the meanings and ways of life of a particular group. For pregnant women who experience a period of constant changes and adaptations, the social setting in which they live and the cultural history indicate which knowledge and dietary practices are good for health maintenance. The following study aimed to understand the cultural influences on the dietary behavior of pregnant women. For such, field research has been chosen, with a qualitative approach and ethnographic aspects. The method of ethnonursing through participant observation and interviews allowed the identification and understanding of meanings, beliefs, and habits that determine dietary behavior of pregnant women. Participants were three pregnant women with gestational age less than 30 weeks, living at northern Santa Maria, Rio Grande do Sul and assisted by the nurses during the prenatal period. The study setting included the nursing clinic and the home of the women. Data collection happened from March to May 2010 after the approval by the Ethics in Research of the Universidade Federal de Santa Maria. The results brought up three categories: "from knowledge to flavors: the eating habits of pregnant women"; "between wishes and possibilities: the dietary adaptations during pregnancy", and "gestational weight gain: a look at the disease, a look at the vanity . It was highlighted that the dietary behavior of pregnant women is interwoven with multiple cultural meanings. The memory, traditions, social and family relations, the media, and the idea of health, illness and aesthetics represent central points for the food conformations. The nurse performing prenatal care, paying attention to the culture of women and their families, sees the motivation for food choices and may thus reorient or maintain the consumption of certain foods, and identify and prevent possible nutrition risks. By valuing dietary practices and the meanings assigned to food, the nurse puts together, strategically, the professional knowledge to popular knowledge, focusing on cultural care to pregnant women.